2012
DOI: 10.1016/j.econlet.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Chinese firms’ political connection, ownership, and financing constraints

Abstract: We empirically examine some listed Chinese firms' political connection, ownership, and financing constraints. Politically-connected firms display no financing constraints whereas firms without connection experience significant constraints. Non-connected family-controlled firms bear greater constraints than non-connected state-owned firms.JEL classification: E22, G31, G18, O16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 6 publications
3
80
0
1
Order By: Relevance
“…Li et al (2008) find that China's private enterprises' party membership can help them to obtain more loans from banks and other state agencies [40]. Chan et al (2012) tested the relationship between political connection and financing constraints. They found that, compared with firms without political connection, politically-connected firms experience less financing constraints [19].…”
Section: The Roles Of Political Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2008) find that China's private enterprises' party membership can help them to obtain more loans from banks and other state agencies [40]. Chan et al (2012) tested the relationship between political connection and financing constraints. They found that, compared with firms without political connection, politically-connected firms experience less financing constraints [19].…”
Section: The Roles Of Political Connectionmentioning
confidence: 99%
“…The first channel refers to the decision-making logic where the politically-connected board chairmen behave similarly to government officials [18] and push listed companies to invest more in ECER to achieve the government's goal. The second channel suggests that since political connection can bring resources to listed companies [19,20], companies may invest more in ECER in return. Due to the existence of these two channels, we can argue that listed companies with politically-connected board chairmen will invest more in ECERI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the fact that development in the legal system is lagging behind comparatively, rent-seeking behaviour is commonly found among government authorities, and thus relations with the government are important to enterprises. Political connections can help Chinese enterprises, especially private enterprises, to gain special resources, such as financing convenience and preferential tax treatment, from the government (Yu and Pan, 2008;Wu et al, 2009;Chan et al, 2012). However, some studies show that political connections have reduced the information quality and transparency of Chinese listed companies (Chaney et al, 2011;Yi et al, 2012).…”
Section: 一、 引言mentioning
confidence: 99%
“…As China is a developing country and a transition economy, the government has a deeper influence on the micro economy, and political connections can help enterprises, especially private enterprises, to gain unique resources from the government, especially local government, such as financing convenience (Yu and Pan, 2008;Chan et al, 2012), preferential tax treatment (Wu et al, 2009), tax avoidance (Luo and Wei, 2012), or entry into monopolised industries (Luo and Liu, 2009). However, political connections can reduce the information transparency of a company.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Consistent with previous studies, it also revealed by Shen et al (2015) that political connections are more prevalent in poor governance firms. Some papers look at the interaction between ownership structure (or type) and political connections (Chan et al, 2012;Al-Hadi et al, 2016). Issue on the link between corporate political connections and related party transaction as an expropriation mechanism is also discussed in some papers.…”
Section: Corporate Governance and Equity Ownership Structurementioning
confidence: 99%